2003
DOI: 10.1590/s1517-83822003000100010
|View full text |Cite
|
Sign up to set email alerts
|

Species identification, slime production and oxacillin susceptibility in coagulase-negative staphylococci isolated from nosocomial specimens

Abstract: Ninety-two coagulase negative staphylococci (CNS) (forty-five of clinical origin and forty-seven of environmental origin), collected in a hospital in San Luis, Argentina, from March to June, 1999, were identified to species level by the ID 32 Staph and API Staph System (bioMérieux). Slime production was investigated by the quantitative and qualitative methods. Oxacillin susceptibility was determined by the disk diffusion test (1 µg), the agar dilution method (0.125 to 4 mg/ml) and agar screen (6 µg/ml). The pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
13
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 26 publications
8
13
0
Order By: Relevance
“…Other CNS species were also identified, including S. cohnii, S. saprophyticus, S. warneri, S. haemolyticus, S. xylosus, S. capitis, and S. lugdunensis. Similar results have been reported in other studies [35,36]. The finding of S. epidermidis as the most frequently isolated species in most studies might be due to the fact that this microorganism possesses certain mechanisms that favor its adaptation to some sites, with this species being the most prevalent bacterium in human skin and mucosa [37].…”
Section: Discussionsupporting
confidence: 86%
“…Other CNS species were also identified, including S. cohnii, S. saprophyticus, S. warneri, S. haemolyticus, S. xylosus, S. capitis, and S. lugdunensis. Similar results have been reported in other studies [35,36]. The finding of S. epidermidis as the most frequently isolated species in most studies might be due to the fact that this microorganism possesses certain mechanisms that favor its adaptation to some sites, with this species being the most prevalent bacterium in human skin and mucosa [37].…”
Section: Discussionsupporting
confidence: 86%
“…Similar biofilm production by CNS strains isolated from different sources, including clinical specimens, environment and microbiota of healthy individuals, has also been reported by other investigators [35,38]. …”
Section: Discussionsupporting
confidence: 85%
“…It is reported that slime factor production in S. aureus isolates from mastitis cause antibiotic resistance which is due to the decreased diffusion of antibiotics through the biofilm matrix and decreased metabolic activity of bacteria (4,36). Several phenotypic methods such as standard tube method, Christensen’s method, Congo Red Agar and microdilution methods are used to detect slime production (2). In the present study, slime producing S. aureus isolates were detected on Congo Red Agar (CRA) plates in vitro.…”
Section: Discussionmentioning
confidence: 99%